2010
DOI: 10.1104/pp.109.148676
|View full text |Cite
|
Sign up to set email alerts
|

VisuaLRTC: A New View on Lateral Root Initiation by Combining Specific Transcriptome Data Sets  

Abstract: Lateral root initiation and development has been increasingly studied over the last two decades. This postembryonic organogenic process guarantees the spatial development and plasticity of the root system in response to environmental cues and is crucial for the plant's growth and development. Several independent large-scale transcriptome studies in different species resulted in a wealth of data that can be instructive to understand this process at the molecular level. Here, we present an easy and flexible spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 30 publications
3
79
0
1
Order By: Relevance
“…This is in agreement with the expression data that could be extracted from the existing data sets that additionally revealed that the auxin-induced expression was dependent on IAA14/SLR and occurs in auxin-treated pericycle cells (see Supplemental Fig-ures 3A to 3C online) (Vanneste et al, 2005;De Smet et al, 2008;Parizot et al, 2010). Additionally, transcript profiling of an arf7 arf19 double mutant identified LBD18 as a downstream target of the ARF7 and ARF19 pathway, as indicated by the lack of auxin inducibility of LBD18 in the arf7 arf19 double mutant (see Supplemental Figure 3D online) (Okushima et al, 2005;Parizot et al, 2010). Taking all these data together, we postulate that LBD18 plays a role in activating the cell cycle during de novo root formation by acting on E2Fa transcription.…”
Section: Lbd18 Binds the E2fa Promoter And Is Induced Upon Lateral Rosupporting
confidence: 74%
See 2 more Smart Citations
“…This is in agreement with the expression data that could be extracted from the existing data sets that additionally revealed that the auxin-induced expression was dependent on IAA14/SLR and occurs in auxin-treated pericycle cells (see Supplemental Fig-ures 3A to 3C online) (Vanneste et al, 2005;De Smet et al, 2008;Parizot et al, 2010). Additionally, transcript profiling of an arf7 arf19 double mutant identified LBD18 as a downstream target of the ARF7 and ARF19 pathway, as indicated by the lack of auxin inducibility of LBD18 in the arf7 arf19 double mutant (see Supplemental Figure 3D online) (Okushima et al, 2005;Parizot et al, 2010). Taking all these data together, we postulate that LBD18 plays a role in activating the cell cycle during de novo root formation by acting on E2Fa transcription.…”
Section: Lbd18 Binds the E2fa Promoter And Is Induced Upon Lateral Rosupporting
confidence: 74%
“…As E2F transcription factors are well-known key regulators of cell cycle initiation, we examined whether the expression of any of the three classical E2F transcription factors of Arabidopsis correlated with lateral root initiation by means of available microarray data sets (Okushima et al, 2005;Vanneste et al, 2005;De Smet et al, 2008;Parizot et al, 2010). Synchronous lateral root initiation can be achieved through auxin treatment of roots pretreated with the auxin transport blocker 1-naphthylphthalamic acid (NPA) (Himanen et al, 2002(Himanen et al, , 2004Vanneste et al, 2005;De Smet et al, 2008).…”
Section: E2fa Is Involved In Lateral Root Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Visual Lateral Root Transcriptome Compendium (VLRTC; Parizot et al, 2010) based on a gene expression atlas of the Arabidopsis root (Brady et al, 2007), we found 95 genes commonly up-regulated more than 2-fold in xylem and lateral root cap (LRC) compared with root tissues not undergoing PCD (Supplemental Table S6). Eight of these genes are among the 154 genes identified by Genevestigator as coexpressed with at least two out of seven genes in the target gene set, significantly more than expected by chance (P = 1.5267e-06, hypergeometric test).…”
Section: Identification Of Unique Dpcd Indicator Genesmentioning
confidence: 99%
“…A positive impact of auxin on the CMT3 expression has also been reported by others (Parizot et al 2010;Shemer et al 2015). In support of the auxin-controlled expression of CMT3 is the presence of the auxin-responsive motif, AuxRE, in the promoter of this gene (http://arabi dopsi s.med.ohio-state .edu/Atcis DB/), which implies that ARFs, the core elements of auxin signalling that are believed to play roles in SE induction in Arabidopsis (Weijers and Wagner 2016;Wójcikowska and Gaj 2017), might regulate CMT3 in response to auxin treatment.…”
Section: Both the Maintenance And De Novo Pathways Of Dna Methylationmentioning
confidence: 59%